(untitled) (Medical Forum Monthly, 2024)
Objective: The aim of this study was to determine spectrum of clinical and Laboratory diagnosis of Systemic lupus erythematosus at tertiary care unit. Study Design: Descriptive type, (cross sectional). Place and Duration of Study: This study was conducted at the Department of General medicine and Paediatric Medicine in indoor and outpatients CMC, Shaheed Muhatarma Benazir Bhutto University Medical Larkana from February 2010 to February 2012. Materials and Methods: We studied prospectively 44 patients with SLE who were seen consecutively either as inpatients or outpatients. All were met the American College of Rheumatology (formerly American Rheumatism Association, ARA) revised criteria for SLE and underwent medical interview as well as routine general physical examination by a researcher, and the laboratory investigations were carried out from single laboratory of Larkana, all these characteristics features of patients were collected in a protocol form. These investigations were includes the CBC, serology for ANA, anti dsDNA and urine for protienuria. X-ray chest and echocardiography was also done for pleural and pericardial effusion. Results: Forty-four patients fulfilled the ACR criteria for SLE, most common presentation were cutaneous 30 (68.2%) cases, mucocutaneous ulceration 26 (59.1%), Fever 26 cases (59.1%), pallor 47 (67.14), cough 34(48.57%), swelling of body 12(17.14%), headache in 10 (22.7%) and Major physical signs were arthritis and arthralgia 30 (68.2%), Hepatosplenomegaly 20 (45.5%), generalized lymphadenopathy 12(27.3%), pleural effusion 08 (18.2%)and 02 (4.5%)patients had pericardial effusion, Raynaud’s phenomenon 10 (22.7%), while direct comb test, ANA, anti dsDNA antibodies were found to be positive in 10 (22.7%), 42 (95.5%), 34(77.3%) cases respectively. Conclusion: Most patients presented almost universally with fever and arthralgias or arthritis in combination with malar rash or oral ulcers and in some patients a combination of all of the above was observed. A combination of positive anti nuclear antibody test, increased ESR and proteinuria were found to be a sensitive and cost effective set of laboratory findings for the diagnosis of patients suffering from SLE. The set of these clinical and laboratory features would help in the correct and early diagnosis of patients suffering from SLE, a relatively rare disease, in the busy medical outpatient and inpatient departments in our set up.